Isolation of microalgal strain from algal-bacterial aerobic granular sludge and examination on its contribution to granulation process during wastewater treatment in respect of nutrients removal, auto-aggregation capability and EPS excretion. (December 2019) - Nuramkhaan, Marjangul; Zhang, Yihao; Dong, Xiaochuan; Huang, Wenli; Lei, Zhongfang; Shimizu, Kazuya; Zhang, Zhenya; Utsumi, Motoo; Lee, Duu-Jong
Abstract: Nutrients removal together with auto-aggregation capability of an isolated microalgal strain Chlorella sp. A-1 from mature algal-bacterial granules was examined under illumination at a light/dark cycle of 12 h/12 h or 0 h/24 h. Then its contribution to granulation process was evaluated in sequencing bath reactors(SBRs). The strain Chlorella sp. A-1 with a fast biomass growth and high auto-aggregation index(82.4% on day 5) achieved 93–96% of N and P removals when treating wastewater containing 50 mg-NH4 -N/l and 5 mg-PO4 -P/l after 5-day cultivation at the light/dark cycle of 12 h/12 h. The inoculated strain Chlorella sp. A-1 in SBRs was observed to help the fluffy activated sludge to transform into a little bit tight structure initiating the formation of algal-bacterial granules. Total extracellular polymeric substances(EPS), especially tightly bound EPS excreted from the strain was found to contribute more to algal aggregation. The isolated Chlorella sp. A-1 is probably the crucial biological factor for algal-bacterial granule formation. Graphical abstract: Unlabelled Image Highlights: One algal strain Chlorella sp. A-1 was isolated from manure algal-bacterial AGS. The isolated A-1 exhibited 93–96% of N and P removal at light/dark cycle of 12 h/12 h. The isolated A-1 grew very fast with a high auto-aggregation index of 82.4%. Algal auto-aggregation index had a strongly positive correlation with EPS content.